AAN position statement: The COVID-19 pandemic and the ethical duties of the neurologist. (28th July 2020) - Rubin, Michael A.; Bonnie, Richard J.; Epstein, Leon; Hemphill, Claude; Kirschen, Matthew; Lewis, Ariane; Suarez, Jose I.
Abstract : Patients, clinicians, and hospitals have undergone monumental changes during the coronavirus disease 2019 (COVID-19) pandemic. This crisis has forced us to consider the obligations that we neurologists have to our individual patients as well as the greater community. By returning to our fundamental understanding of these duties, we can ensure that we are providing the most ethically appropriate contingency and crisis care possible. We recommend specific adaptations to both the inpatient and outpatient settings, as well as changes to medical and trainee education. Furthermore, we explore the daunting but potentially necessary implementation of scare resource allocation protocols. As the pandemic evolves, we will need to adapt continuously to these rapidly changing circumstances and consider both national and regional standards and variation.